The Requirement of Records Management Practices for Institutional Audits - Nurul Emyliana Nik Ramlee, Nik; Farik Mat Yatin, Saiful; Md Zali, Mastura; Aiqa Mohd Zain, Nurul; Abu Bakar, Amzari; Satirah Wan Mohd Saman, Wan; Ahmad Iskandar Raja Yaacob, Raja (International Journal of Engineering and Technology, 2018)
Currently, the issues of corruption or white-collar crime rise in government sector and this issue raised during the audit checking. The organization itself do not take the initiative and follow the policy and standard assigned by the government when manage the records in their organization with the requirement of records management practices. This study also emphasizes the role of records management in conducting the risk mitigation in governance regarding the auditing process, the relationship of the records management and good governance and to analyse the general report of one organization in Malaysia which related with the audit department. With this study, hopefully the good governance and accountability could be achieved and the crime rate could be minimized as well as no litigation occur during the auditing process if the records management practices plays their roles. This study is to investigate the impact of the implementation of good records management practice in exercising good governance and to ease up the auditing process.Â Â